2000
DOI: 10.1177/002246690003400303
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Indicators of Written Expression Proficiency for Middle School Students

Abstract: In this study we examined the reliability and validity of various growth indicators in written expression for middle school students. In addition, we examined the effects of type and duration of writing on the validity and reliability of the growth indicators. Students ( N = 112) in Grades 7 and 8 composed two story writing and two descriptive writing pieces. For each sample, students wrote for 3 and 5 minutes. The most reliable and valid predictor of student writing proficiency as measured by both teacher rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
5
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 18 publications
9
110
5
1
Order By: Relevance
“…They are also argued to be a sensitive index of pupil's written text production (Espin et al, 2000) and have been successfully used to examine the skills of English language learners (Campbell, Espin, & McMaster, 2013).…”
Section: Curriculum Based Measures Of Writingmentioning
confidence: 99%
“…They are also argued to be a sensitive index of pupil's written text production (Espin et al, 2000) and have been successfully used to examine the skills of English language learners (Campbell, Espin, & McMaster, 2013).…”
Section: Curriculum Based Measures Of Writingmentioning
confidence: 99%
“…Criterionrelated validity estimates were less strong in Gansle et al (2002) with small to moderate correlations between the Iowa Test of Basic Skills Total Score and CWS (r = .43), and Louisiana Educational A ssessm ent Program (Write Competently subscale) with TWW (r = .28) and CWS (r = .28). Although less re searched than TWW and CWS, CIWS also has evidence of technical adequacy including valid ity estimates exceeding production-dependent measures (Espin et al, 2000), and similar re sults have been found for the productionindependent indicator of %CWS (Amato & Watkins, 2011;McMaster & Espin, 2007).…”
Section: Methodsmentioning
confidence: 55%
“…The following measures have been found to be reliable: total words written, words spelled correctly, and correct writing sequences (e.g., Espin, Scierka, Skare, & Halverson, 1999;Espin et al, 2000).…”
Section: Reliabilitymentioning
confidence: 99%